Touchscreen controls for future flight deck design: investigating visual parameters on human-computer interactions between pilot flying and pilot monitoring - Li, Wen-Chin; Korek, Wojciech Tomasz; Liang, Yung-Hsiang; Lin, John J. H. (Aeronautical and Astronautical Society of the Republic of China, 2023)
This study is concentrated on investigating the different visual behaviors and HCI patterns between pilot flying and pilot monitoring while interacting with touchscreen controls on the flight deck. Twelve participants with flight experiences (M=1150, SD=4019.9) attended this research. The apparatus included Future Systems Simulator (FSS), eye tracker, and system usability scale (SUS). The designated scenario in the experiment was an instrument landing. All participants were required to perform two instrument landings in two different roles, pilot flying (PF) and pilot monitoring (PM). The order of role of randomized to eliminate practice effects. The results revealed that fixation counts of pilot flying were different among four AOIs, F (3, 9) = 10.58, p = .003, η_p^2 = .78. On the other hand, the FC of pilot monitoring demonstrated a significant difference among four AOIs, F (3, 8) = 8.69, p = .007, η_p^2 = .77. There was a significant difference between PF and PM on the subjective assessment of SUS total score, t (11) =3.85, p = 0.003, Cohen's d= 1.11. The application of a touchscreen can integrate input and output in the same area for visual feedback. There is a rising need to simplify the future flight deck design based on the principle of human-centered design. Conclusion: The application of touchscreen flight controls may have the potential to facilitate single-pilot operations flight deck design in the future. TSCs considerations must be consistent with human information processing and pilots' operational characteristics on the future flight deck.
Keywords: Future System Simulator; Human-Computer Interactions; System Usability; Touchscreen Controls; Visual Attention